A Randomized Trial of Topical Anesthesia Comparing Lidocaine Versus Lidocaine Plus Xylometazoline for Unsedated Transnasal Upper Gastrointestinal Endoscopy - Justin Cheung; Karen J Goodman; Robert Bailey; Richard N Fedorak; John Morse; Mario Millan; Tom Guzowski; Sander Veldhuyzen van Zanten (Canadian Journal of Gastroenterology)
BACKGROUND: The optimal topical anesthesia regimen for unsedated transnasal endoscopy is unknown. The addition of a nasal decongestant, such as xylometazoline (X), to a topical anesthestic may improve patient comfort.